Prevalence and risk factors for placenta previa in a specialty hospital - Mara Elisa Monterde-Fernández; Joel Jahaziel Díaz-Vallejo; Iliana Rodríguez-Parissi; Berenice Venegas-Espinoza; Ezri Cruz-Perez (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: Placenta previa is a risk factor for obstetric hemorrhage, which, if not managed, can lead to maternal and neonatal death. Most cases are diagnosed after 28 weeks of gestation; in many cases, prenatal diagnosis is not timely. The objective of this study was to estimate the prevalence of placenta previa and its risk factors. Methods: A retrospective case-control study was carried out with a total of 35 cases and 138 controls among pregnant women. The variables studied were previous cesarean section, BMI, abortions, uterine surgeries and maternal age, among others. The chi-square test was used to examine differences between groups; the OR was calculated for each factor via univariate and multivariate analyses. Results: The prevalence of placenta previa was 0.57%. The risk factors identified were advanced maternal age (OR 3.0; 95% CI 1.3-7.1) and previous cesarean section (OR 10.7; 95% CI 1.7-68.5). Conclusion: The prevalence of placenta previa was similar to that reported in the literature, and the most prevalent risk factors were advanced maternal age and previous cesarean section. The identification of risk factors in women with placenta previa makes it possible to establish action plans for personalized care during pregnancy and childbirth and to reduce complications.